Strengthening FeCrNiCu high entropy alloys via combining V additions with in-situ TiC particles. (1st April 2021) - Wu, Hao; Huang, Sirui; Zhu, Heguo; Xie, Zonghan
Abstract: The combined effects of vanadium additions and in-situ TiC particle formation upon the microstructure and mechanical properties of FeCrNiCu high entropy alloys were investigated. The addition of V changed the FeCrNiCu matrix structure from FCC (i.e., face-centered cubic) to FCC+BCC (i.e., body-centered cubic). The as-cast 10 vol.%TiC/FeCrNiCuV0.1 high entropy alloy matrix composite showed excellent mechanical properties, with the yield strength and ultimate tensile strength determined to be 653.5 MPa and 1006.5 MPa, respectively. The extra strength generated by V addition and in-situ TiC particles in FeCrNiCu was evaluated, and the theoretical predictions match the experimental results well. Graphcial abstract: Image, graphical abstract